The Guardians - Dolin, Lucy Dougan (2015)
Many poems in this collection explore the intrusions of 'the wild' into daily life, through memories, in illness, and in places that you've lost or left behind. Dougan is interested in the ways in which the past re-enters the present, particularly through the secrets of family life, in all kinds of atavism, and in pockets of wildness in the suburbs and the city which are a source of liveliness and a dark sort of energy. Her poems feature old houses, ruins, revisited places; they focus on the bonds between the generations, between children and adults, humans and animals, and humans and the physical world. The title of the collection refers broadly to these ties, which impose a sense of guardianship on those who are bound by them. In contrast to the wildness they recognise, the poems themselves seek to tread lightly - they aspire to quietness and reticence, to cumulative rather than immediate effects, and to sustaining a relatively natural and unobtrusive voice.